Americas Association of Sarcoidosis and Other Granulomatous Disorders (AASOG) 2024 Conference: The Art of Working Together for Progress (August 15-16, 2024) - AAVV, (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Book of Abstracts